1988
DOI: 10.2307/1222095
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOGEOGRAPHICAL SIGNIFICANCE OF THE OCCURRENCE OF ABIETANE‐TYPE DITERPENOIDS IN SALVIA SECT. ERYTHROSTACHYS (LAMIACEAE)

Abstract: Summary The presence of abietane derived diterpenoids in a few members of the large American Salvia subgenus Calosphace suggests that it may have differentiated from groups ancestral to the Old World salvias or even prior to the differentiation of the groups in Salvia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Morphologically S. tortuosa does not appear to be closely related to the rest of the section (Wood and Harley 1988), therefore further sampling of Colombian Tubiflorae (specifically, S. camaraefolia Benth., S. secundiflora Rusby and S. falcata Wood & Harley) is needed to determine whether any of these species are closely related to S. divinorum and S. venulosa. Biogeography Previous work has concluded that Mexico is the center of diversity (Neisess 1983;Reisfield 1987;Ramamoorthy et al 1988;Harley and Heywood 1992;Walker 2006;Jenks 2009) for the monophyletic (Walker et al 2004;Jenks 2009) subgenus Calosphace and that the South American species and lineages arose from within the Mexican taxa (Walker 2006;Jenks 2009). Previous results (Walker 2006;Jenks 2009) show that there have been multiple long-distance dispersal events from Mexico to South America.…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically S. tortuosa does not appear to be closely related to the rest of the section (Wood and Harley 1988), therefore further sampling of Colombian Tubiflorae (specifically, S. camaraefolia Benth., S. secundiflora Rusby and S. falcata Wood & Harley) is needed to determine whether any of these species are closely related to S. divinorum and S. venulosa. Biogeography Previous work has concluded that Mexico is the center of diversity (Neisess 1983;Reisfield 1987;Ramamoorthy et al 1988;Harley and Heywood 1992;Walker 2006;Jenks 2009) for the monophyletic (Walker et al 2004;Jenks 2009) subgenus Calosphace and that the South American species and lineages arose from within the Mexican taxa (Walker 2006;Jenks 2009). Previous results (Walker 2006;Jenks 2009) show that there have been multiple long-distance dispersal events from Mexico to South America.…”
Section: Discussionmentioning
confidence: 99%